2015
DOI: 10.1021/acs.inorgchem.5b01213
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Octahedral Rotations and Lone Pair Ferroelectricity in CsPbF3

Abstract: CsPbF3 is the only experimentally synthesized ABF3 fluoride perovskite with a polar ground state. We use CsPbF3 as a guide in our search for rules to rationally design new ABX3 polar fluorides and halides from first-principles and as a model compound to study the interactions of lone pairs, octahedral rotations, and A- and B-site driven ferroelectricity. We find that the lone pair cation on the B-site serves to stabilize a polar ground state, analogous to the role of lone pair cations on the A-site of oxide pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 57 publications
1
62
0
Order By: Relevance
“…Geometrical considerations of the local atomic interactions could help elucidate the origin of the observed asymmetry in the Sn-Br correlation. For example, the enlarged perpendicular anisotropic ADPs of the Br atoms could result in a distribution of Sn-Br correlations at and above the nominal Sn-Br bond distance, which would appear as peak tailing to high r. Alternatively, a rhombohedral off-centering of the Sn 2+ (towards the face of the SnBr 6 octahedra along the [111] crystallographic direction) would result in two Sn-Br correlation distances. If this off-centering is dynamic, this could appear as an asymmetric peak at the nominal Sn-Br correlation distance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometrical considerations of the local atomic interactions could help elucidate the origin of the observed asymmetry in the Sn-Br correlation. For example, the enlarged perpendicular anisotropic ADPs of the Br atoms could result in a distribution of Sn-Br correlations at and above the nominal Sn-Br bond distance, which would appear as peak tailing to high r. Alternatively, a rhombohedral off-centering of the Sn 2+ (towards the face of the SnBr 6 octahedra along the [111] crystallographic direction) would result in two Sn-Br correlation distances. If this off-centering is dynamic, this could appear as an asymmetric peak at the nominal Sn-Br correlation distance.…”
Section: Resultsmentioning
confidence: 99%
“…Ca 2+ is chosen for comparison because of its identical ionic radius to Sn 2+ in octahedral coordination, as calculated from bond valence sums in oxides. 77,78 Because effective ionic size depends on the ligands, CsSnBr (200) is presented in Figure 8(b), for the case where Sn 2+ is displaced along [111]. An asymmetric lobe of elevated localization opposite to the direction of cation dis-placement is indicative of the broken inversion symmetry of the lone pair that has become stereochemically active.…”
Section: Ab Initio Studies Of Cubic Cssnbrmentioning
confidence: 99%
“…Nonetheless, none of the reported fluoride candidates belong to the most claimed perovskite family. Recently, we have shown that even if none of the fluoroperovskites is reported with a FE ground state (except CsPbF 3 [11,12]) they have nevertheless the propensity to have a FE instability in their high symmetry cubic reference structure [13]. We have identified that the FE instability of the fluoroperovskites is related to a steric geometric effect when small cations lie at the A-site.…”
mentioning
confidence: 94%
“…Thus, the presence of a lone pair allows the cation to displace off‐center of the polyhedron . Furthermore, Smith et al explained the important role of stereoactivity of Pb lone pair in making CsPbF 3 ferroelectric at room temperature; the authors compare this compound with the nonferroelectric CsSrF 3 , where Sr 2+ has almost the same ionic radius as Pb 2+ but no lone pair.…”
Section: Resultsmentioning
confidence: 99%